Neutrophil gelatinase-associated lipocalin reflects the severity of anemia without iron deficiency and secondary hyperparathyroidism in hemodialysis patients - Yigit, Irem Pembegul; Ulu, Ramazan; Gozel, Nevzat; Taskapan, Hulya; Ilhan, Necip; Dogukan, Ayhan (Kare Publ, 2017)
OBJECTIVE: Secondary hyperparathyroidism (SHPT) and anemia are the primary and most common complications in patients receiving hemodialysis (HD). Neutrophil gelatinase-associated lipocalin (NGAL) is a new marker to assess iron deficiency and manage iron therapy for HD patients. The aim of this study was to determine any association between serum NGAL level and anemia without iron deficiency in patients with SHPT on chronic HD. METHODS: Total of 61 SHPT patients on chronic HD were enrolled in the study and divided into 3 groups: mild SHPT group (n=17), moderate SHPT group (n=21), and severe SHPT group (n=23). Hemogram, biochemical assays, and level of ferritin, high sensitivity C-reactive protein (hs-CRP), and NGAL were evaluated in all groups. RESULTS: Serum NGAL level was significantly higher and hemoglobin (Hb) level was significantly lower in severe SHPT patients compared with both mild and moderate SHPT patients. Furthermore, in severe SHPT group, serum NGAL level was significantly positively correlated with serum parathyroid hormone (r=0.79; p=0.00) and hs-CRP (r=0.52; p=0.01) level and negatively correlated with serum Hb (r=-0.56; p=0.00) level. CONCLUSION: SHPT was important factor affecting anemia in HD patients. Even when iron deficiency anemia is excluded in patients with SHPT, there was significant negative correlation between serum NGAL and Hb.
Keywords: Anemia; hemodialysis; hyperparathyroidism; neutrophil gelatinase-associated lipocalin